Karl Polanyi : prophète de la fin de l’économie libérale - Keith Hart (Revue Interventions Économiques)
The interest for the work of Karl Polanyi has increased with the avent of neoliberal globalization and it may still increase given the catastrophies which follow. In 1944, in his book The Great Transformation, Karl Polanyi explained the difficulties encountered by capitalism between the two wars. They resulted in part from the tendency to try to establish an autoregulating market since the 19 th century. Society reacted to this and opposed this trend. Polanyi expected a rearticulation of economy and society through social planification, but he had not anticipated the development of market economy under leadership of the USA. He then went on to study preindustrial economies, from a formal and substantive point of view. Later on, his concept of embeddedness was central in the emergence of a new Economic Sociology. Today, his analysis of financial capitalism before the first war and the disaster of the period between the two wars is particularly interesting.